AKTIVITAS ANTIOKSIDAN DAN SITOTOKSIK BERBAGAI FASE BUNGA MELASTOMA MALABATHRICUM LINN - Isnaini; Denny Anata Kusuma; Anthony Hermawan; Fujiati; Alfi Yasmina (Jurnal Kesehatan Islam : Islamic Health Journal, 2024)
Abstract. Melastoma malabathricum Linn is one of the medicinal plants, and is used by the community. M. malabathricum L. flowers contain quercetin and kaempferol which have antioxidant and anticancer properties. Each phase of flower M. malabathricum L. has different quercetin and kaempferol contents. This study aims to analyze the differences in antioxidant and toxicity activities of various phases of karamunting flowers by DPPH and brine shrimp lethality (BSLT) methods. Antioxidant activity is expressed by IC50 while toxicity activity is expressed by LC50. IC50 and LC50 are calculated using probit analysis. The blooming phase has the greatest antioxidant and toxicity activity (IC50 6,989 ppm (95% CI 6,358 ± 9,276) and LC50 146,325 ppm (95% CI 101,257 ± 215,766) while bud flower phase 2 has the smallest antioxidant and toxicity activity (IC50 8,866 ppm (95% CI 8.075 ± 9,874) and LC50 233,222 ppm (95% CI 151,662 ± 408,101). Conclusion The flower phase of Melastoma malabatricum Linn has low antioxidant activity, causing its toxic properties to be lower Kata Kunci: flower phases, Melastoma malabathricum Linn; antioxidant; toxicity